The Use of Fractionated Sunflower Lecithins for Encapsulation of Micronutrients - Kalmanovich, Svetlana A. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: The work is dealing with scientific and practical substantiation of the prospects for the use of fractionated sunflower lecithins (FSLs) as an encapsulating agent in relation to hydrophilic and lipophilic physiologically functional micronutrients. Materials and Methods: Studies were conducted on the advanced equipment according to the standard techniques. Evaluation of the obtained results was carried out using contemporary methods of calculation of static reliability. Results: The article presents the results of comparative studies of the composition, physicochemical indicators and ability to form the FSL-based microemulsions produced by the innovative technology, which consists of processing of cover-free sunflower seeds using a reduced impact technology conditions and ethanol as the extractant. Discussion: A certain method is proposed to produce the FSL-based microemulsions with encapsulated hydrophilic and lipophilic micronutrients, consisting of vitamin C and oil solution of Î²-carotene. It is shown that treatment of the FSL-based microemulsion by an electromagnetic field with magnetic induction of 0.5 T during 5 min provides degrees of encapsulation of vitamin C at a level of 83% and Î²-carotene at a level of 100%. Conclusion: The results obtained can underlay the further research on the creation of a range of encapsulated forms of micronutrient premixes.